Pendidikan Dakwah Islam Melalui Design Graphis Media Sosial Pada Kelompok Remaja - Miftakhul Rohman; Hanna Aulia; Feri Hardiansyah (LP3M IAIFA Kediri, 2024)
The participation of the Millennial generation in conveying da'wah is increasingly diverse, one of which is da'wah content that is interesting, creative and in line with the preaching of faith and morals. The presence of increasingly diverse da'wah content provides challenges for teenagers who must continue to hone their abilities in compiling visual images of da'wah so that they are in line with the goals and objectives that have been set. This article tries to provide the results of the service carried out in the form of training in Islamic Da'wah education through graphic design which was organized by the Islamic Media and Broadcasting Department of UNU Blitar in collaboration with the young generation of Gledug village. The participants in this training are a group of young people from Gledug Village who are the millennial generation. Project-based learning is used as a methodological basis in this training by applying the knowledge gained during the instructor's presentation in a mini project in the form of creating lecture content using Canva website tools to create design supporting graphics for participants. The results of the training show that the Gledug village youth group can design da'wah content by paying attention to the relationship between images and the da'wah message they want to convey